Mitochondrial ROS Accumulation Contributes to Maternal Hypertension and Impaired Remodeling of Spiral Artery but Not IUGR in a Rat PE Model Caused by Maternal Glucocorticoid Exposure - Jing Long; Yan Huang; Gang Wang; Zhengshan Tang; Yali Shan; Shiping Shen; Xin Ni (MDPI AG, 2023)
Increased maternal glucocorticoid levels have been implicated as a risk factor for preeclampsia (PE) development. We found that pregnant rats exposed to dexamethasone (DEX) showed hallmarks of PE features, impaired spiral artery (SA) remodeling, and elevated circulatory levels of sFlt1, sEng IL-1β, and TNFα. Abnormal mitochondrial morphology and mitochondrial dysfunction in placentas occurred in DEX rats. Omics showed that a large spectrum of placental signaling pathways, including oxidative phosphorylation (OXPHOS), energy metabolism, inflammation, and insulin-like growth factor (IGF) system were affected in DEX rats. MitoTEMPO, a mitochondria-targeted antioxidant, alleviated maternal hypertension and renal damage, and improved SA remodeling, uteroplacental blood flow, and the placental vasculature network. It reversed several pathways, including OXPHOS and glutathione pathways. Moreover, DEX-induced impaired functions of human extravillous trophoblasts were associated with excess ROS caused by mitochondrial dysfunction. However, scavenging excess ROS did not improve intrauterine growth retardation (IUGR), and elevated circulatory sFlt1, sEng, IL-1β, and TNFα levels in DEX rats. Our data indicate that excess mitochondrial ROS contributes to trophoblast dysfunction, impaired SA remodeling, reduced uteroplacental blood flow, and maternal hypertension in the DEX-induced PE model, while increased sFlt1 and sEng levels and IUGR might be associated with inflammation and an impaired energy metabolism and IGF system.